AI-Driven Digital Platforms for Rural Entrepreneurship: Enabling Inclusive Growth and Economic Empowerment for a Viksit Bharat - Yadav, Sudha Ramashray (Journal of Advanced Research in Information Technology, Systems and Management, 2025)
India’s rural economy significantly contributes to the nation’s GDP while sustaining a large portion of its population. However, it faces persistent challenges, such as inadequate infrastructure, limited financial access, and restricted market opportunities, which hinder rural entrepreneurship. This study explores how artificial intelligence (AI) and data analytics can address these challenges by enabling informed decision-making, fostering innovation, and enhancing operational efficiency. AI-driven solutions—such as demand forecasting, market intelligence, supply chain optimisation, and financial inclusion— empower rural entrepreneurs to overcome systemic barriers. By creating a robust, inclusive ecosystem, AI can play a pivotal role in achieving sustainable and equitable growth, advancing India’s vision of a technologically empowered Viksit Bharat.